1993
DOI: 10.1159/000244013
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Small Intestinal Glutaminase and Glutamine Synthetase in the Rat: Response to Dexamethasone

Abstract: The ontogeny of small intestinal glutaminase (GA) and glutamine synthetase (GS) was studied with relation to the maternal administration of dexamethasone (DEX). Pregnant Sprague-Dawley rats were administered 0.2 mg/kg of DEX or saline twice daily on days 19 and 20 of gestation. Activity of GA did not increase from the fetus to the 10-day-old rat; however, GS activity increased 7-fold. DEX induced doubling of GA activity and mRNA, but only a slight increase is GS activity and mRNA was observed in the fetus. GA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Glutaminase activity in the small intestine of rats was shown not to change for up to 10 days after birth [9]. However, by the end of the suckling period [10] and by the time of weaning [8] the activity of glutaminase in epithelial cells from the rat small intestine had increased.…”
Section: Introductionmentioning
confidence: 91%
“…Glutaminase activity in the small intestine of rats was shown not to change for up to 10 days after birth [9]. However, by the end of the suckling period [10] and by the time of weaning [8] the activity of glutaminase in epithelial cells from the rat small intestine had increased.…”
Section: Introductionmentioning
confidence: 91%
“…Whereas, human intestinal cells can also convert glutamate into glutamine, this process is limited due to the low glutamine synthetase activity in the small intestine (89,90). In the neonatal period, this ability may be further limited as studies in young rats demonstrated that glutamine synthetase activity is particularly low in the pre-weaning period (91,92). Remarkably, IECs as well as immune cells cannot function properly without the availability of exogenous glutamine (93).…”
Section: Metabolism Of Glutamine and Glutamate In Intestinal Epithelimentioning
confidence: 99%